Ozaukee County, Wisconsin, Lake Michigan coastline GIS visualization - Wortley, A. J. (My University, 2003)
This zip file contains GIS files (project files, executables and data formats) for purposes of understanding how such data can be archived. All of these files are part of an existing and functioning GIS project. The project is being developed to visualize the Lake Michigan coastline for Ozaukee County.
Keywords: Lake Michigan; Ozaukee County, Wisconsin; ArcView project; GIS dataset; coastline visualization